Rehabilitation and release of confiscated songbirds into the wild: A pilot study - Cruz, Cláudio Estêvão Farias; Driemeier, David; Sonne, Luciana; Pavarini, Saulo P.; Panziera, Welden; Funkler, Gustavo R.; Böelter, Nicole S.; Homem, Juan L. C.; Soares, Camila E. S.; Tres, Gabrielle Z.; Silva, Vitor G. C.; Correa, Miguel L.; et al. (Frontiers in Veterinary Science, 2023)
Songbirds are currently the most prevalent animals in illegal trafficking in Brazil and other countries, so they are often confiscated, and this poses legal, ethical, and conservation challenges. Returning them to nature requires complex and expensive management, a topic that is sparingly addressed in the literature. Here, we described the processes and costs associated with an attempt to rehabilitate and release confiscated songbirds into the wild. A total of 1,721 songbirds of several species were quarantined, rehabilitated, and released, primarily on two farms located within their typical geographical distribution. Health assessments were performed on samples from 370 birds. Serology revealed no antibodies against Newcastle disease, and Salmonella spp. cultures were negative. Real-time polymerase chain reactions detected M. gallisepticum in samples from seven birds. Atoxoplasma spp. and Acuaria spp. infections, sepsis, and trauma were the top causes of bird death. About 6% of the released birds were recaptured, within an average period of 249 days after release, and at a mean distance of 2,397 meters from the release sites. The majority of these birds were found with free-living mates within or close to fragments of transitional ecoregions with native or cultivated grasslands, and native groves/forests, and shrublands. However, eucalyptus plantations with rich understory regeneration provided a suitable environment for the released forest species to settle, since they were recaptured during the defense of these sites. Over half of the recaptured birds presented behavioral profiles with both dominant and tame traits. Birds with dominant traits are more likely to settle in habitats and face the live decoys during fieldwork, whereas birds with tame characteristics tend to accept close contact with humans. Ultramarine grosbeak (Cyanoloxia brissonii), the least common species among those released, at the release sites showed an almost 2-fold recapture rate in the shortest mean distances from the release sites. This suggests less territory competition, perhaps a major factor of bird re-establishment here. The total per-bird cost was USD 57. Our findings suggested suitable survival and re-establishment of confiscated songbirds in the wild, when managed as we describe.